2016
DOI: 10.5194/hess-20-4801-2016
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends and variability in river discharge across northern Canada

Abstract: Abstract. This study presents an analysis of the observed inter-annual variability and inter-decadal trends in river discharge across northern Canada for 1964–2013. The 42 rivers chosen for this study span a combined gauged area of 5.26  ×  106 km2 and are selected based on data availability and quality, gauged area and record length. Inter-annual variability in river discharge is greatest for the eastern Arctic Ocean (coefficient of variation, CV  =  16 %) due to the Caniapiscau River diversion into the La Gr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 111 publications
(96 citation statements)
references
References 73 publications
3
92
1
Order By: Relevance
“…These results show that continued increasing annual discharge into the HBC is expected, as in recent observations (Déry et al, ). Discharge is likewise projected to increase across other northern regions (Canadian Arctic, Québec, Eurasia, and Scandinavia) through the 21st century (Guay et al, ; Koirala et al, ; Shkolnik et al, ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results show that continued increasing annual discharge into the HBC is expected, as in recent observations (Déry et al, ). Discharge is likewise projected to increase across other northern regions (Canadian Arctic, Québec, Eurasia, and Scandinavia) through the 21st century (Guay et al, ; Koirala et al, ; Shkolnik et al, ).…”
Section: Discussionsupporting
confidence: 90%
“…The Hudson Bay Drainage Basin (HBDB) comprises over a third of the Canadian landmass, accounts for over a fifth of freshwater exports into the pan-Arctic Ocean system via the Hudson Bay Complex (HBC; McClelland et al, 2006) and contains important hydroelectric infrastructure and agriculture (Abelson, 1985;Hassanzadeh et al, 2014). HBDB discharge, which has increased since the late-1980s (Déry et al, 2016), also influences circulation, sea ice dynamics, and biological and biogeochemical processes within the HBC (Macdonald & Kuzyk, 2011). Such coastal ocean systems are considered among the most sensitive marine environments to climate change Mackenzie et al, 2004).…”
Section: Citationmentioning
confidence: 99%
“…The decrease in Ω by mixing with river water, especially with Mackenzie River water, which has high [Ca 2+ ] and TA, is smaller than mixing with SIM. In 1997, a direct inflow of Mackenzie River water into the central Canada Basin was observed (Déry et al, ; Macdonald et al, , ; Woo & Thorne, 2003) and the freshening did not lower TA and Ω significantly (Figures e and d ) . In contrast, the freshening by SIM between 2005 and 2007 accounted for a decrease in Ω by 0.15 (Figure e).…”
Section: Resultsmentioning
confidence: 94%
“…Significant seasonal warming of up to 2 °C was found in 1997, 2008, and 2012 which increased Ω by ~0.1 (Figure d). In 1997, high seawater temperatures were observed in southern region, which was due to the intrusion of warm Mackenzie River runoff directly into the central Canada Basin (Déry et al, ; Macdonald et al, , ; Woo & Thorne, ). In 2008 and 2012, high surface temperature was due to early opening of the sea ice (Kwok et al, ) that allowed much more absorption of solar radiation in July when sunlight is more intense closer to the summer solstice (Light et al, ; Skyllingstad & Polashenski, ).…”
Section: Resultsmentioning
confidence: 99%
“…However, previous studies have shown that climatic effects are spatially diverse and can vary even within a single river system. For instance, the Mackenzie River in western Canada has not displayed significant long‐term discharge trends at its basin outlet (at 67.5°N) since 1973 (Déry, Stadnyk, MacDonald, & Gauli‐Sharma, ). However, the Athabasca River (at 56.7°N), one of its most southern headwater tributaries originating in the Rocky Mountains, has been experiencing decreasing streamflows since the early 1970s (Peters, Atkinson, Monk, Tenenbaum, & Baird, ); whereas, its other tributaries in permafrost regions, such as those in the lower Liard Valley (at 61.7°N), have experienced increased runoff (Connon, Quinton, Craig, & Hayashi, ).…”
Section: Introductionmentioning
confidence: 99%